2003
DOI: 10.1007/s00167-003-0362-y
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically assisted meniscal allograft transplantation with and without combined anterior cruciate ligament reconstruction

Abstract: The menisci provide a vital role in load transmission across the knee joint as well as contribute to knee stability, particularly in the ACL-deficient knee. Loss of the meniscus, in part or in total, significantly alters joint function and predisposes the articular cartilage to degenerative changes, which has been well documented both clinically and radiographically. This study examined clinical and patient-reported outcomes following meniscal allograft transplantation with and without combined ACL reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 64 publications
3
77
1
Order By: Relevance
“…17 The number of previous knee operations was only described in three of the studies identified. [18][19][20] Whilst many review articles proffer that surgical results are best in those patients with Outerbridge Grade 3 or less chondral damage (Table 1), very few studies actually describe pre-operative grades for their patient subsets. Only two papers identified radiographic criteria used for assessing suitability for the procedure.…”
Section: Reviewmentioning
confidence: 99%
“…17 The number of previous knee operations was only described in three of the studies identified. [18][19][20] Whilst many review articles proffer that surgical results are best in those patients with Outerbridge Grade 3 or less chondral damage (Table 1), very few studies actually describe pre-operative grades for their patient subsets. Only two papers identified radiographic criteria used for assessing suitability for the procedure.…”
Section: Reviewmentioning
confidence: 99%
“…Standard meniscal suture repair methods were employed to suture the margin of the meniscus to the capsule and attach the meniscal allograft (5,16). Vertical sutures are typically employed to attach the meniscus from the rear 1/3 to the front in all cases and this was performed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…GonzalezLucena et al 176 performed MAT with suture fixation without any bone block and found a high rate of complications (33%) and revision surgery. Yoldas et al 177 examined clinical and patient-reported outcomes following meniscal allograft transplantation with bony fixation performed with bone plugs for medial transplants and using a bone bridge for lateral transplants.…”
Section: Meniscus Repair and Replacementmentioning
confidence: 99%